Inventory Replenishment Policy For Linear Symmetric Demand - Ma, hao-wei (2016)
This research focuses on minimizing the summation of holding costs and ordering costs for a linear symmetric demand over a given time horizon. Since it is difficult to determine each reorder moment when the demand rate firstly increases and later falls, we choose to use a fixed time interval with a different replenishment quantity in each time. This method overcomes the difficulty of using Silver-Meal heuristic or any other traditional methods of calculating linear symmetric demand. Two numerical examples are provided to illustrate how simple the proposed method is. The total cost is 3% higher than Silver’s result in the case of initial demand equaling zero, but 1.3% lower than Silver’s result in the case of when initial demand is not zero. In addition, this solution procedure is much easier than Silver’s method and it is better to keep a constant order interval with suppliers since it may need more communications and extra cost when the interval is different from one to another.